Fiscal Policy Instruments For Reducing Congestion And Atmospheric Emissions In The Transport Sector : A Review - Timilsina, Govinda R. (The World Bank, 2008)
This paper reviews the literature on the fiscal policy instruments commonly used to reduce transport sector externalities. The findings show that congestion charges would reduce vehicle traffic by 9 to 12 percent and significantly improve environmental quality. The vehicle tax literature suggests that every 1 percent increase in vehicle taxes would reduce vehicle miles by 0.22 to 0.45 percent and CO2 emissions by 0.19 percent. The fuel tax is the most common fiscal policy instrument; however its primary objective is to raise government revenues rather than to reduce emissions and traffic congestion. Although subsidizing public transportation is a common practice, reducing emissions has not been the primary objective of such subsidies. Nevertheless, it is shown that transport sector emissions would be higher in the absence of both public transportation subsidies and fuel taxation. Subsidies are also the main policy tool for the promotion of clean fuels and vehicles. Although some studies are very critical of biofuel subsidies, the literature is mostly supportive of clean vehicle